Oaxaca-Blinder as a Reweighting Estimator - Kline, Patrick (American Economic Review, 2011)
The classic regression based estimator of counterfactual means studied by Ronald Oaxaca (1973) and Alan Blinder (1973) is shown to constitute a propensity score reweighting estimator based upon a linear model for the conditional odds of being treated.